Área foliar, assimilação de carbono e fotoquímica da fotossíntese de duas cultivares de mangueira (Mangifera indica L.) sob diferentes intensidades de sombreamento ou temperatura - Araújo, Eugênio Celso Emérito (Universidade Federal de São Carlos, 2006)
The physiology of mango is little known in relation to other fruit trees. There are gaps about estimation of mango leaf area using no destructive methods or concern photosynthetic responses under temperatures above 10oC, carbon assimilation, leaf and bud productions inr shade. The aims of present work were to shed light on these gaps determining on mango cultivars Tommy Atkins and Haden a) Indexes and equations for fast and no-destructive estimate leaf area (AF) just using length (C), maximum width (L), or both; b) Photosynthetic capacity, leaf and bud production growing under 0, 65 and 85% of shade and, c) The photosynthetic responses (photochemical and photosynthetic capacities) under temperatures between 17-32o C. The leaf area (AF) could be estimated multiplying length x width x 0,74 (for Tommy cultivar) or 0,78 (for Haden) as well using equations: AF = 4,96349 C - 33,429 (R2=0,86); AF = 17,02964 L - 18,88065 (R2=0,85) and AF = 0,73499 (CxL) + 0,59459 (R2=0,92) for Tommy or AF = 5,35282C - 33,17061(R2=0,88); AF = 19,09951L - 24,61777(R2=0,89) and AF = 0,76015(CxL) + 0,43257(R2=0,99) for Haden. In shade the cultivars presented same values of maximum net photosynthesis (Amax) obtained under full solar irradiance, decreasing the light compensation point and/or increasing the chlorophyll content. Besides, until 65% of shade, both cultivars maintained the same leaf and bud production in relation to full solar irradiance treatment, enabling them for plantation under high densities until middle shade intensities (around 65%). The optimum temperature range for Amax was 23-29oC in Tommy and 23-26oC in Haden. Both cultivars presented an unbalance between photochemical and biochemical phases of the photosynthesis in between 17-32o C, especially Haden. Under regular atmospheric concentration of CO2 the net photosynthesis of Haden, in general, was smaller than Tommy, while under CO2 saturation the opposite happened, possibly because Haden used its largest capacity of electron transport to increase the carbon assimilation, and, at the same time, decreasing its susceptibility to oxidative stress. Both cultivars presented high temperature adaptation maintaining almost constant the intensities of dark respiration (Rd) in Tommy and the photorespiration (Pr) in Haden. In Tommy Pr induced increases in light saturation (LS) and compensation (LCP) points, and reductions in apparent quantum yield (α). In Haden increases in Rd, LS stability and α reductions with temperature did not keep relationship with Pr nor with RE probably because the rupture of the cellular homeostasis caused by high electron excess.
Keywords: Fisiologia vegetal; Ecofisiologia; Manga; Fotossíntese; Respiração; Temperatura; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL